TESTOSTERONE AND PHYSICAL ACTIVITY: A REVIEW OF HORMONAL VARIABILITY IN SEDENTARY AND ACTIVE MEN - Joanna Katarzyna Pergoł; Julia Sposób; Adam Borsuk; Martyna Narożniak; Zuzanna Krupa; Bartłomiej Czerwiec; Adrianna Ewa Pękacka; Julia Borkowska; Malwina Wojtas; Julia Skowrońska-Borsuk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Testosterone (T) is the main androgenic-anabolic hormone in men, playing a vital role in reproductive function, muscle and bone maintenance, mood regulation, and metabolic health. Its levels are dynamic and modulated by both intrinsic and extrinsic factors, notably physical activity. While sedentary behaviour is associated with age-related hormonal decline, various forms of exercise may induce either beneficial or adverse endocrine adaptations. The purpose of this review is to analyze how different types of physical activity—and inactivity—affect T levels in adult men, and to explore the physiological and behavioural modulators of these responses.Materials and Methods: A thorough review of the literature available on PubMed and Google Scholar databases was conducted using the following keywords: “testosterone”, “testosterone levels”, “physical activity”, “sedentary”, “resistance training”, “endurance training”, “testosterone in athletes”, “overtraining syndrome”, and “exercise-hypogonadal male condition”. Peer-reviewed studies published between 1987 and 2025 were included, with a focus on both clinical and physiological investigations examining acute and chronic T responses to various forms of physical activity in adult males. Special attention was given to studies addressing modulating factors such as age, energy availability, circadian rhythms, stress, and sleep quality.Summary and Conclusions: Resistance training tends to acutely elevate and chronically sustain T concentrations. In contrast, prolonged endurance training may lead to suppressed baseline testosterone – EHMC. Factors like low energy availability, stress, and aging further influence hormonal patterns. Recognizing these variations is essential for clinicians, coaches, and researchers to properly interpret T data and avoid unnecessary medical interventions.